APPLICATION OF MODALITY AND MOOD TO UNDERSTAND THE DIALOGUE IN SERIES SCRIPT: A STUDY OF DISCLAIMER - Masrif, Dewi Farnila (Jurnal Bahasa Asing, 2025)
This research analyzes the application of modality and mood in the dialogue of the Disclaimer series to create narrative tension. Through this analytical approach, this study aims to explore how modality verbs, word choice, and mood patterns are used to build emotions and tension that affect the audience's perception of characters and situations. By using a qualitative descriptive method, in obtaining data, the author took data from dialog in the form of phrases, clauses or sentences through dialog transcriptions from each episode of the Disclaimer series, where modality is used by using modal verbs, expressions of possibility and necessity. The results showed that there were 14 expressions containing elements of Deontic and Epistemic modality namely obligation, permission, possibility and probability used in conversational sentences in the Disclaimer series combined with moods such as declarative, imperative, and interrogative, able to create a tense atmosphere.